Faktor-faktor yang Mempengaruhi Belanja Modal pada Provinsi di Sumatera dan Jawa - Kareena Priangka Putri; Choiruddin; Okky Savira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This purpose of this study to determine how capital expenditure in the 16 provinces located in Sumatra and java from 2019 to 2023 is influenced by locally generated revenue, special allocation funds, and the remaining budget surplus. The sampling technique used in this research is saturated sampling. This research utilizes secondary data and hypothesis testing tools using the statistical Product and Service Solutions (SPSS) software versions 26, with the data analysis method employed being multiple linier regression. The partial hypothesis test results show that regional original revenue and budget surplus have a positive and significant effect on capital expenditure. In contrast, special allocation funds have a negative and significant effect on capital expenditure. Simultaneously, the results indicate that regional original revenue, special allocation funds, and budget surplus, collectively hava a positive and significant influence on capital expenditure.